2015
DOI: 10.1309/ajcpeie12poiculi
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Needle Aspiration Diagnoses of Noninvasive Follicular Variant of Papillary Thyroid Carcinoma

Abstract: If NFVPTCs were no longer termed carcinomas, this would affect the rate of malignancy of FNA diagnostic categories. Cytologic and molecular features could aid in identifying NFVPTCs at the time of FNA diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
154
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 114 publications
(171 citation statements)
references
References 37 publications
14
154
0
3
Order By: Relevance
“…To determine whether this distinction can be made in a reliable manner, we prospectively classified aspirates originally diagnosed as ''suspicious for malignancy'' or ''malignant'' using criteria we had previously identified as helpful in distinguishing between NIFTP/FVPTC and cPTC (8). These criteria were sufficient to permit classification as either NIFTP/FVPTC or cPTC in 87.5% (49/56) of cases with accurate distinction between cPTC and other follicular patterned lesions (including NIFTP, FVPTC, and follicular adenoma) in 94% (46/ 49) of classified cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether this distinction can be made in a reliable manner, we prospectively classified aspirates originally diagnosed as ''suspicious for malignancy'' or ''malignant'' using criteria we had previously identified as helpful in distinguishing between NIFTP/FVPTC and cPTC (8). These criteria were sufficient to permit classification as either NIFTP/FVPTC or cPTC in 87.5% (49/56) of cases with accurate distinction between cPTC and other follicular patterned lesions (including NIFTP, FVPTC, and follicular adenoma) in 94% (46/ 49) of classified cases.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, members of our group published the results of a small pilot study retrospectively comparing the cytologic features of NIFTP with those of cPTC (8). The results of this study showed that NIFTP was more likely diagnosed as suspicious for malignancy rather than malignant on cytology and demonstrated a microfollicular predominant architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that a majority of NIFTP cases are sequestered within the indeterminate categories of TBSRTC leading to a significant impact on the implied ROM [8,9,10,11]. It remains to be seen how NIFTP will be incorporated into thyroid pathology and affect management algorithms.…”
Section: Selected General Issues Of Tbsrtcmentioning
confidence: 99%
“…Bizzarro et al13 concluded that NIFTP usually lacks pseudoinclusions and papillary structures; nuclear size and microfollicular clusters may allow differentiation between NIFTP and invasive FVPTC. Howitt et al17 found statistically significant differences in cytomorphologic features between patients with NIFTP and those with PTC. In their series, among PTC cases, 96% demonstrated tumor sheets, 50% had papillae, 79% had pseudoinclusions, and microfollicles were noted in only 4% of cases.…”
Section: Introductionmentioning
confidence: 97%